Modeling human age-associated increase in Gadd45γ expression leads to spatial recognition memory impairments in young adult mice - Brito, David V. C.; Gülmez Karaca, Kübra; Kupke, Janina; Mudlaff, Franziska; Zeuch, Benjamin; Gomes, Rui; Lopes, Luísa V.; Oliveira, Ana (Neurobiology of aging, 2020)
Aging is associated with the progressive decay of cognitive function. Hippocampus-dependent processes, such as the formation of spatial memory, are particularly vulnerable to aging. Currently, the molecular mechanisms responsible for age-dependent cognitive decline are largely unknown. Here, we investigated the expression and function of the growth arrest DNA damage gamma (Gadd45γ) during aging and cognition. We report that Gadd45γ expression is increased in the hippocampus of aged humans and that Gadd45γ overexpression in the young adult mouse hippocampus compromises cognition. Moreover, Gadd45γ overexpression in hippocampal neurons disrupted cAMP response element-binding protein signaling and the expression of well-established activity-regulated genes. This work shows that Gadd45γ expression is tightly controlled in the hippocampus and its disruption may be a mechanism contributing to age-related cognitive impairments observed in humans.
Gesehen am 12.11.2020